GENDER INEQUALITY AND WOMEN’S INCLUSIVENESS IN POLITICS: AN ASSESSMENT OF THE 2024 LOCAL GOVERNMENT ELECTION IN ADAMAWA STATE - SHARON EMMANUEL NTASIRI; ROGERS ROLAND WAZAKARI; TAKUR’AMA NEVISON ZIDON (International Studies Journal)
The study examines gender inequality and women’s inclusiveness in politics in 2024 local government election in Adamawa State. Despite global strides in promoting women’s political inclusiveness, research consistently demonstrates that women often remain on the periphery of politics, with low participation in government structures and the democratic process, particularly developing countries. The study adopts liberal feminist theory. The study employs descriptive research design to examine gender inequality and women's inclusiveness in politics during the 2024 local government elections in Adamawa State. Purposive sampling techniques was used. Data collected were analysed using chi-square facilitated by SPSS. The study discovered that there is high rate of women participation and inclusion in 2024 local government election in Adamawa State. The study recommends that state and local government should continue to expand and create awareness programmes that promote gender equality and women participation in politics.